Perceived corporate social responsibility (CSR) activities and the antecedents of customer loyalty in the airline industry - Asatryan, Roman; Asamoah, Emmanuel Selase (Univerzita Pardubice, 2014)
In today’s world of business, consumers are increasingly expecting firms to engage in CSR and managers see it as marketing for competitive advantage. For the firms in the airline industry, their interest is how current and potential consumers would evaluate their CSR activities and more importantly whether it could lead to the creation of more loyal customers. The main objective of this study is to examine the impact of perceived corporate social responsibility (CSR) activities on the antecedents of customer loyalty among customers in the airline industry. The quantitative cross sectional research design was employed to measure the effects of CSR activities on the antecedents of customer loyalty (customer satisfaction, product quality, company image, consumer trust). A web-based survey was used to collect data. A total of 500 respondents from different age groups, sex and educational background were selected. The data was analysed using the multiple regression statistical analysis. It was found that CSR has a positive effect on all of the four antecedents of customer loyalty. With regards to the strength of prediction, it was found that customer trust had the strongest effect. This was followed by the image of the firm, customer satisfaction and product quality.
Keywords: corporate social responsibility; customer loyalty; customer satisfaction; product quality; company image; consumer trust